Estruturas ministeriais comparadas: Uma análise preliminar sobre a trajetória de ministérios em 21 países (1990-2020) - Silvana Santos Gomes; Luciana Dutra de Oliveira Silveira; Jaqueline da Silva Borges; Noëlle Da Silva; Jo\~ao Cláudio Basso Pompeu; Igor Ferraz Da Fonseca; Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Ministries are government structures that are located at the intersection between cycles of public policies, political party relations and the organizational design of direct public administration. Despite their relevance, the trajectory of the ministries over time is poorly understood, with an explanatory gap persisting as to the factors that lead to the creation, stability, transformation and extinction of these structures. Faced with this gap, this Discussion Paper sought to address the following central question: is there an underlying pattern to the trajectory of ministerial structures in different countries? To this end, a comparative analysis of the trajectories of ministries pertaining to 21 countries over a period of thirty years (1990-2020) was undertaken, with the aim of capturing convergent and divergent dynamics in view of the political systems of the countries studied and the thematic areas of the ministries. Preliminary findings indicate that ministries are strongly prone to stability regardless of the political system of the country in question, while changes in competence are the most frequent category of transformation. In addition, the longest running ministries are those with thematic areas related to the structuring activities of the State, such as justice and foreign affairs
Keywords: D73; H11; 330; ministry structures; administrative organization; institutional trajectory; comparative analysis